Enhanced lunar semidiurnal equatorial vertical plasma drifts during sudden stratospheric warmings - Fejer, B. G.; Tracy, B. D.; Olson, M. E.; Chau Chong Shing, Jorge Luis (Geophysical Research Letters, 2011)
Large scale electrodynamic and plasma density variations in the low latitude ionosphere have recently been associated with sudden stratospheric warming (SSW) events. We present empirical models of largely enhanced lunar semidiurnal equatorial vertical plasma drift perturbations during arctic winter low and high solar flux SSW events. These perturbations play a dominant role in the electrodynamic response of the low latitude ionosphere to SSWs. Our models indicate that the amplitudes of the enhanced lunar semidiurnal drifts are strongly local time and solar flux dependent, with largest values during early morning low solar flux SSW periods. These results suggest that ionospheric conductance strongly modulate low latitude ionospheric changes during SSWs. They also indicate that lunar semidiurnal effects need to be taken into account by global ionospheric models for their improved forecasting of the low latitude ionospheric response to SSW events, especially for low solar flux conditions. Por pares